Effect of long term treatment with metoprolol and sotalol on ventricular repolarisation measured by use of transoesophageal atrial pacing. Issue 2 (February 1986) - Blomström-Lundqvist, C; Dohnal, M; Hirsch, I; Lindblad, A; Hjalmarson, A; Olsson, S B; Edvardsson, N
Abstract : The effects of long term (4 weeks) treatment with oral metoprolol (100 mg twice daily) and sotalol (160 mg twice daily) on ventricular repolarisation time were compared in a double blind crossover study in 20 patients post-infarction. For QT interval studies transoesophageal atrial pacing was performed at a cycle length of 800 ms. Sotalol prolonged the QT interval by 5-7% compared with metoprolol. The prolongation reflects a change in the repolarisation time because there was no change in the QS interval. Measurements of heart rate at rest and during bicycle exercise indicated that metoprolol and sotalol in the doses selected were equipotent as beta blockers. Transoesophageal atrial pacing is a simple non-invasive method with few and mild side effects that is well suited to drug studies.